Pengembangan Video Pembelajaran Menggunakan Sparkol Videoscribe Pada Materi Pelaminan Pengantin Jawa - Erinda Asrie Mega Bintang; Lilies Yulastri; Lilis Jubaedah (Universitas Negeri Jakarta, 2024)
This development research was conducted to produce sparkol-based Videoscribe media as an alternative learning media for the Special Make-up Room Decoration Art course on the Javanese Bridal Stage material. The research method used is Research and Development (R&D) which is developed through the ADDIE model. The research sample was students who had taken the Special Make-up Room Decoration Art course. The data collection method used was a questionnaire. The results of the data analysis showed that the developed media was feasible to use, seen from the validation of media experts 90% (very valid) and material experts 88.33% (very valid). This practicality test was conducted on 20 students who had taken the special make-up room decoration art course, based on the practicality test table, a percentage of 84.66% was obtained, including in the